Rancang Bangun Sistem Informasi Manajemen Operasional Dilengkapi dengan Penjualan Sparepart pada Bengkel MJM - Richard Soegiarto; Soetam Rizky Wicaksono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
MJM is a leading workshop in Malang that focuses on car repairs and is known for its reliable reputation and quality service on Jl. Lake Tondano Raya F5/A26, Sawojajar. These workshops offer a variety of services, from engine to car body repairs, which makes manual transactions difficult and time-consuming due to increased service and cost complexity. This research aims to simplify transaction and operational processes in MJM workshops by developing supporting applications that include recording customer transactions, spare parts stock management, monitoring employee attendance, and mechanic payroll. The information technology provided can improve service quality, optimize operations, strengthen competitiveness, enable a sustainable approach, increase data accuracy, and support more timely decisions. The methodology used is waterfall, which follows a certain flow process starting from requirements analysis, planning, design, software development, testing, to the maintenance stage. The research focus is on the initial development of the system to ensure that the system functions well in the maintenance phase. The Operational Management Information System designed for MJM workshops includes important features such as recording spare parts, purchase and sale transactions for spare parts, service and car wash transactions, stock taking records, management of damaged or lost goods, stock cards, cash flow, and reports. transaction. This system is expected to reduce manual errors, provide better service, and improve overall operational performance.